Long Non-Coding RNA HOXA Transcript Antisense RNA Myeloid-Specific 1–HOXA1 Axis Downregulates the Immunosuppressive Activity of Myeloid-Derived Suppressor Cells in Lung Cancer - Tian, Xinyu; Ma, Jie; Wang, Ting; Tian, Jie; Zhang, Yue; Mao, Lingxiang; Xu, Huaxi; Wang, Shengjun (Frontiers in Immunology, 2018)
HOXA transcript antisense RNA myeloid-specific 1 (HOTAIRM1) is a long non-coding RNA that has been shown to be a key regulator of myeloid cell development by targeting HOXA1. Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that possess immunosuppressive function. However, the impact of HOTAIRM1 on the development of MDSCs remains unknown. In this study, we demonstrated that HOTAIRM1 was expressed in MDSCs and that over-expression of HOTAIRM1 could down-regulate the expression of suppressive molecules in MDSCs. In addition, HOTAIRM1 levels were observed to be decreased in the peripheral blood cells of lung cancer patients compared to those of healthy controls. By analysing HOTAIRM1 expression levels in different types of lung cancer, we found that HOTAIRM1 was mainly expressed in lung adenocarcinoma. Finally, it was confirmed that HOTAIRM1 could enhance the expression of HOXA1 in MDSCs and that high levels of HOXA1, the target gene of HOTAIRM1, could delay tumour progression and enhance the anti-tumour immune response by down-regulating the immunosuppression of MDSCs. Taken together, the present study illustrates that HOTAIRM1/HOXA1 down-regulates the immunosuppressive function of MDSCs and may be a potential therapeutic target in lung cancer.